Estimation of the tax potential as a part of budgetary potential - Zhebchuk, Roman (Lviv Polytechnic Publishing House, 2015)
The author describes the method calculating of tax potential in the process of budget planning as part of the budgetary potential.
Keywords: budgetary potential; budget planning; public finance; fiscal potential; structure of budgetary potential